IMPLEMENTASI TEKNOLOGI DAN MEDIA DALAM LAYANAN BIMBINGAN DAN KONSELING - Agungbudiprabowo; Fadhila Kiranasari; Lola Febriyanti (Jurnal Selaras : Kajian Bimbingan dan Konseling serta Psikologi Pendidikan, 2021)
The purpose of this study is to provide an overview of the importance of implementing technology and media in guidance and counseling. The method used in this study used literature studies with data analysis techniques in the form of content analysis. Study results can be used as reference material for guidance and counseling teachers in schools, or guidance and counseling students in developing guidance and counseling service media.